Monitoring and analysis of PM10 concentration at Delhi Metro construction sites. (2015) - Mishra, Rajeev Kumar; Joshi, Tarun; Goel, Nikhil; Gupta, Himanshu; Kumar, Amrit
Among all critical air pollutants, particulate matter pollution (PM10 ) is being awarded greater significance over the past decade. Along with vehicular traffic and meteorological phenomenon, construction works are the major source for release of PM10 in the atmosphere. It is a major source for acute, chronic and respiratory health problems. It produces short term as well as long term health problems in day-to-day lifestyle. This study aims to collect real time particulate matter data from metro construction sites to understand the gravity of the particulate matter pollution due to metro construction works. EPAM HAZ 5000 dust sampler is used to conduct the field studies and record the particulate matter (PM10 ) levels at Badli, Mayapuri and Najafhgarh metro construction sites of Delhi, India. The results report alarmingly high levels of particulate matter pollution, i.e., 245 ppm (during peak hours), 222 ppm (during peak hours) at Najafgarh and Mayapuri metro construction sites respectively, with time weighted average of PM10 concentration exceeding the national ambient air quality standards (24 hr) of 100 µg/m 3 .